2014
DOI: 10.1080/03075079.2014.894016
|View full text |Cite
|
Sign up to set email alerts
|

How are task reflexivity and intercultural sensitivity related to the academic performance of MBA students?

Abstract: How are task reflexivity and intercultural sensitivity related to the academic performance of MBA students? Higher Education in business school environments is increasingly focused on how to best equip students with the skills necessary for leadership in the global workplace. This paper examines the impact of two particularly important cognitive capabilitiestask reflexivity and intercultural sensitivity, on academic performance in an MBA programme. It was hypothesised that in an intercultural learning environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…However, teaching creativity has proved to be far from easy (Kaufman, 2018). Accordingly, including intercultural competencies in university syllabuses (Jones, 2013;Lyubovnikova, Napiersky, & Vlachopoulos, 2015) can be a suitable option to improve creativity in an indirect way. Therefore, seeking ways to channel acquisition of both creativity and interculturality must be a priority in higher education, as their interrelationship can yield very important benefits for students 2016; Lee, Therriault, & Linderholm, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, teaching creativity has proved to be far from easy (Kaufman, 2018). Accordingly, including intercultural competencies in university syllabuses (Jones, 2013;Lyubovnikova, Napiersky, & Vlachopoulos, 2015) can be a suitable option to improve creativity in an indirect way. Therefore, seeking ways to channel acquisition of both creativity and interculturality must be a priority in higher education, as their interrelationship can yield very important benefits for students 2016; Lee, Therriault, & Linderholm, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Van der Poel (2016) reported that the ICs were predictive of students' intercultural development during a stay abroad. Furthermore, Lyubovnikova et al (2015) found that intercultural sensitivity as measured by the IRC predicted the degree to which students appreciated their group's cultural diversity as a resource for learning and performance.…”
Section: Intercultural Competences (Ics)mentioning
confidence: 99%
“…Ingols and Shapiro (2014) focus on the assessment of soft skills in terms of teamwork, leadership, and ethics. Lyubovnikova et al (2015) outline the importance of task reflexivity and intercultural sensitivity in enhancing the academic performance of students. Further perspectives include the importance of commitment and satisfaction of students (Wilkins et al , 2016), the role of faculty in academic excellence (Shukla and Singh, 2016), etc.…”
Section: Relevant Literaturementioning
confidence: 99%